Answer:
Alexander is incorrect because the expressions are not equivalent.
Step-by-step explanation:
If the expression is evaluated for any value of x, y; the result will not be same.
For instance, let assume x = 1 and y = 2
3x + 4y = 3 + 4 = 7
(3)(4) + xy = (3)(4) + (1 * 2) = 12 + 2 = 14
So, the expressions are not the same and Alexander is incorrect.
Hello :
<span>y = 2(x + 3)² - 5
y = 2(x²+6x+9) -5
y = 2x² +12x +13...(answer : </span><span>A) y=2x^2+12x+13 )</span>
Answer:
A. 2 distinct roots.
Step-by-step explanation:
2x^2 + 8x + 3 = 0
Finding the discriminant:
b^2 - 4ac = 8^2 - 4 * 2 * 3
= 64 - 24
= 40
The discriminant is positive but not a perfect square
So there are 2 distinct ,real, irrational roots.
Since the parabola is connecting the points, it means that the points given are on the parabola or that the points are solutions of the parabola. Thus, when we substitute the points into the function, we should end up with the correct y-value.
To find the correct choice, let's test a point. An easy point to test I believe would be (-3, 0) because we should be getting 0 as a y-value. Let's test:
![A. (- 3 - 3)(3 + 4) = -42](https://tex.z-dn.net/?f=A.%20%28-%203%20-%203%29%283%20%2B%204%29%20%3D%20-42)
![B. (-3 + 3)(-3 - 4) = 0](https://tex.z-dn.net/?f=B.%20%28-3%20%2B%203%29%28-3%20-%204%29%20%3D%200)
![C. (-3 + 2)(-3 - 4) = 7](https://tex.z-dn.net/?f=C.%20%28-3%20%2B%202%29%28-3%20-%204%29%20%3D%207)
![D. (-3)(-3 + 12) = -27](https://tex.z-dn.net/?f=D.%20%28-3%29%28-3%20%2B%2012%29%20%3D%20-27)
We can see that Choice B is the correct function, because it produces 0 when we substitute
. Thus, Choice B, or (x + 3)(x - 4) is the answer.